Describing God? (Brill, 2025)
This volume engages traditional and contemporary approaches to the Divine attributes in Christian-Muslim dialogue. A particular focus lies on the attributes of omnipotence and omniscience, justice and mercy, as well as simplicity and divine action. Engaging these attributes comparatively, two questions are posed: How can these attributes be conceived today, and to what extent is a mutual learning across religious traditions possible? Thereby, a special focus is placed on the role of analytic philosophy. How do the philosopical ‘language games‘ used contribute to communicability across religions?